2017
DOI: 10.1177/1526924817715460
|View full text |Cite
|
Sign up to set email alerts
|

Does Having a Relative in Dialysis Therapy Affect Attitudes Toward Kidney Donating?

Abstract: The attitudes of the relatives of individuals undergoing dialysis treatment toward kidney donation were determined to be more positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(31 reference statements)
0
6
0
3
Order By: Relevance
“…A study conducted in Turkey 27 reported that 78% of individuals in households considered organ donation as a gift of life to the others. In another study from Turkey, 15 participants who had a relative receiving dialysis treatment were willing to donate their kidney was found significantly higher than the rate of the participants who had no relative receiving dialysis treatment. We think that this result may differ according to the countries and cultural characteristics.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…A study conducted in Turkey 27 reported that 78% of individuals in households considered organ donation as a gift of life to the others. In another study from Turkey, 15 participants who had a relative receiving dialysis treatment were willing to donate their kidney was found significantly higher than the rate of the participants who had no relative receiving dialysis treatment. We think that this result may differ according to the countries and cultural characteristics.…”
Section: Discussionmentioning
confidence: 84%
“…Although this difference was not found to be statistically significant, it was similar in keeping with previous studies. 15,20 In El-Shoubaki and Bener's study, 21 majority of the participants from Qatari population preferred organ donating for their close relatives. In Rios et al's study from Spain, 16 respondents that had previous organ donation experience through family had a more favorable opinion towards organ donation than who had not had any experience.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…16 Topbaş ve Taştan'ın yürüttüğü bir çalışmada da diyaliz tedavisi gören bir akrabası olan bireylerin böbrek nakline yönelik daha pozitif tutum gösterdikleri belirlenmiştir. 26 Bu bulgular, yakınında organ yetmezliği olan bireylerin, organ yetmezliğine bağlı yaşanan problemleri yakınlarında bizzat görmeleri ve sevdikleri kişileri kaybetme korkusu nedeni ile konuya daha duyarlı bakmalarından kaynaklanabilir.…”
Section: Organ Bağişi Tutum öLçeği̇unclassified